2022
DOI: 10.1186/s13567-022-01074-5
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete autophagy promotes the proliferation of Mycoplasma hyopneumoniae through the JNK and Akt pathways in porcine alveolar macrophages

Abstract: Autophagy is an important conserved homeostatic process related to nutrient and energy deficiency and organelle damage in diverse eukaryotic cells and has been reported to play an important role in cellular responses to pathogens and bacterial replication. The respiratory bacterium Mycoplasma hyopneumoniae has been identified to enter porcine alveolar macrophages, which are considered important immune cells. However, little is known about the role of autophagy in the pathogenesis of M. hyopneumoniae infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It was reported that M. gallisepticum synthesizes hydrogen peroxide to initiate lipid peroxidation of host cell membrane, thereby compromising the integrity and permeability of the eukaryotic cell membrane and facilitating bacterial entry [ 26 ]. Other mycoplasmas are diverse and may involve cellular pathways or endocytic mechanisms [ 27 , 28 ].…”
Section: Invasion and Transmissionmentioning
confidence: 99%
“…It was reported that M. gallisepticum synthesizes hydrogen peroxide to initiate lipid peroxidation of host cell membrane, thereby compromising the integrity and permeability of the eukaryotic cell membrane and facilitating bacterial entry [ 26 ]. Other mycoplasmas are diverse and may involve cellular pathways or endocytic mechanisms [ 27 , 28 ].…”
Section: Invasion and Transmissionmentioning
confidence: 99%
“…M. hyopneumoniae employs the JNK and Akt signaling pathways to induce incomplete autophagy in porcine alveolar macrophages. Incomplete autophagy serves as a defense mechanism, impeding the entry of M. hyopneumoniae into lysosomes and preventing its degradation, allowing the proliferation of M. hyopneumoniae within porcine alveolar macrophages (Wen et al, 2022). Lipid rafts also seem to be involved in mycoplasma invasion, it possibly associated with caveola-dependent endocytosis (Quest et al, 2004).…”
mentioning
confidence: 99%